Code Switching for English Language Teaching and Learning in EFL Classroom - Widya Adhariyanty Rahayu (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2015)
Indonesia is a multilingual and multicultural country. The language situation in Indonesia is very complex because Indonesia has many tribes and also a lot of vernacular languages. English language plays an essential role in a multilingual society. Teaching English is not easy task so that is why the educator needs stratergy to teach English as a Foreign Language (EFL). The educator has big influences to reach the students’ comprehend the materials. In the process of teaching and learning English, one of the best ways is using code switching. Code switching is a valuable strategy in assisting English language teaching and learning procedure, particularly at the basic level of English language. This paper sets out the concept and the function of code switching for English language teaching and learning in EFL classroom.